Spirituality and the Therapeutic Recreation Practitioner: Exploring the Implications for Practice and Research - Angela Wozencroft, PhD; Steven N. Waller Ph.D.; Gene A Hayes; Larry Brown (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2012)
There is a growing body of literature that relates to spirituality and leisure. Within this corpus, several scholars continue to address the relationship between spirituality and therapeutic recreation. Much of the available literature chronicles the health and wellness benefits that accrue to the client/participant but little attention has been devoted to understanding the relationship between the personal spirituality of the therapeutic recreation (TR) professional and its influence on service delivery. The purpose of this essay was three-fold: (1) to examine the influence of spirituality in the work lives of TR practitioners; and (2) to chronicle existing literature that relates to spirituality and TR practitioners; and (3) to provide a discussion on the need for additional research to better understand the relationship between spirituality and the manner in which therapeutic recreation services are provided. We concluded that further exploring the relationship between the spirituality of TR professionals and its impact on practice is a viable line of scholarship that should be pursued vigorously.
Keywords: Leisure; spirituality; recreation; therapeutic recreation; faith based